Seven new species of the genus Diochus Erichson (Coleoptera: Staphylinidae, Staphylininae, Diochini) - Huang, Tian; Janák, Jiří; Zhou, Hong-Zhang; Ge, Si-Qin (Zootaxa, 2026)
Seven new species of the genus Diochus Erichson, 1839 (Coleoptera: Staphylinidae, Staphylininae, Diochini) are described in this paper: Diochus quadraticeps sp. nov. and D. sinuatus sp. nov. from Thailand; D. moluccanus sp. nov. from Indonesia; D. ullrichi sp. nov. and D. madangensis sp. nov. from Papua New Guinea; D. insularis sp. nov. from China (Taiwan, Hongkong), Japan, Mauritius, Reunion and Rodriguez; D. parvoculatus sp. nov. from Peru. Photographs and line drawing plates for each new species are provided.